Conditions for balance between survival and ruin - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Let ξ_t be a classic risk process or a risk process with stochastic premiums. We establish conditions for balance between ruin and survival in the case of zero initial capital u = 0 (ruin probability q_+ = ψ(0) = 1/2, survival probability p_+ = 1 — q_+ = 1/2) and determine premium estimates under these conditions.